Phosphate-based solid glass ceramic electrolytes for rechargeable lithium-ion/air batteries - Toh, Kang Hui. (2012)
Water-stable superionic lithium glass-ceramic electrolyte (GCE) system Li2O-Al2O3-GeO2-P2O5 (LAGP) was successfully prepared by melting and quenching method. A novel vitreous phase has been prepared by introducing boron oxide (B2O3), a renowned glass former in the parent LAGP system, which tends to increase the stabilization of the amorphous glass structure. Thus prepared LAGP – xB2O3 (x = 0.0 – 0.4 wt.%) system has been systematically investigated by differential scanning calorimetry (DSC), X-ray diffraction (XRD), field emission scanning electron microscope (FE-SEM), nuclear magnetic resonance (NMR), and ionic conductivity studies in the wide temperature range -30 – 100ºC. The ionic conductivity of grain boundary is observed to be maximum ~ 3.2 × 10-3 S cm-1 at 30 °C for the LAGP GCEs sintered at 850 °C for 12 h as compared to the samples sintered at other temperatures. An optimum amount of B2O3 (x = 0.3) adding on the conductivity of the LAGP system, shows very high thermal stability as well as σgb ~ 8.75 × 10-3 S cm-1 (higher by a factor of 3) at 30 °C. The highest σgb of LAGP – 0.3B2O3 is attributed to higher defect density and Li+ ion mobility achieved in the appropriate composition of LAGP and B2O3. In most cases low activation energy (~ 0.18 – 0.74 eV) for lithium transport was observed. It can be inferred that the B2O3-added LAGP electrolytes would be a hopeful candidate for all-solid-state battery because of simplistic preparation by the B2O3 addition, relatively high Li ion conductivity, and good interfacial stability against Li metal. Lithium nitride (Li3N) is well-known to provide the interfacial stability/interface with respect to lithium foil has also been added to the parent LAGP system to investigate its effects on stabilization of amorphous glass structure and its ionic conductivity.